1996
DOI: 10.1177/039139889601900805
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistula Obstruction and Expression of Platelet Receptors for Von Willebrand Factor and for Fibrinogen (Glycoproteins GPIb and GPIIb/llla) in Hemodialysis Patients

Abstract: Platelet surface receptors for von Willebrand factor and for fibrinogen (glycoproteins GPIb and GPIIb/IIIa) were studied with monoclonal antibodies CD42 and CD41 and cytofluorometry in 31 healthy subjects, 10 hemodialysis patients with no A-V fistula obstruction (patent original fistula), 10 hemodialysis patients with frequent A-V fistula obstruction (more than twice), 12 patients with mild chronic renal failure (creatinine 1.75 +/- 0.40 mg/100 ml), 11 patients with advanced chronic renal failure (creatinine 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…GPIIb/IIIa is the receptor for fibrinogen that has been identified as the pivotal mediator of platelet aggregation [26] . PAC1 is an activated but unoccupied GPIIb/IIIa complex that is one of the markers of platelet activation [6] .…”
Section: Discussionmentioning
confidence: 99%
“…GPIIb/IIIa is the receptor for fibrinogen that has been identified as the pivotal mediator of platelet aggregation [26] . PAC1 is an activated but unoccupied GPIIb/IIIa complex that is one of the markers of platelet activation [6] .…”
Section: Discussionmentioning
confidence: 99%
“…This antigen is a part of the platelet adhesion receptor gpIb/V/IX which binds subendothelial von Willebrand factor and it is internalized after platelet activation 13 . The expression of this receptor was enhanced in uremic patients with an increased risk of occlusion of arteriovenous fistulae 23 . In addition, ligand‐induced binding sites (LIBS‐1) epitopes were detected far more frequently on platelets from patients with primary biliary cirhhosis and primary sclerozing cholangitis? 13 These neoepitopes are unraveled by conformational changes in the integrin receptors gp IIb/IIIa by physiological stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Liani et al 7 studied platelet surface receptors for von Willebrand factor and fibrinogen (glycoproteins, GPIb, and GPIIb/IIIa) with monoclonal antibodies of CD41 and CD42. They detected a significant increase in platelet surface glycoproteins (GPIb and GPIIb/IIIa) in hemodialysis patients with frequent AV fistula…”
Section: Discussionmentioning
confidence: 99%
“…7 Knoll et al 8 recently studied the role of thrombophilia in hemodialysis patients in order to determine whether thrombophilia was associated with AV fistula or graft thrombosis. They reported that 59 patients with access thrombosis (55%) had at least 1 thrombophilia compared with 122 patients without access thrombosis (39%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation